PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBLITY, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, TERHADAP KINERJA KEUANGAN - Hadiani, Intania; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Financial performance is the determination of the certain sizes which can measure the success of an organization or a company in generating profit. This research is meant to study the influence of the disclosure of corporate social responsibility, managerial ownership, institutional ownership, to the financial performance in the manufacturing companies which are listed in Indonesia Stock Exchange. The sample of this research is the manufacturing companies which are listed in Indonesia Stock Exchange in 2011-2014 periods. The sample collection method has been done by using purposive sampling method and 13 sample companies have been obtained as the research object. The data analysis technique has been done by using multiple linear regressions. The result of partial test shows that the disclosure of corporate social responsibility and institutional ownership has significant influence to the financial performance whereas the managerial ownership does not have any significant influence to the financial performance.Keywords: Disclosure of corporate social responsibility, managerial ownership, institutional ownership, financial performance.